2017
DOI: 10.1007/s11085-017-9825-2
|View full text |Cite
|
Sign up to set email alerts
|

Hot Corrosion of Ti–Re Alloys Fabricated by Selective Laser Melting

Abstract: Selective laser melting (SLM) is an additive manufacturing process that enables novel alloy production by combining metals with significantly different physical properties. In this paper, the hot corrosion behavior of Ti-Re alloys fabricated by SLM was studied in a mixture of Na 2 SO 4 and NaCl salts at 600°C. The morphology and composition of the corrosion products were characterized by scanning electron microscopy with energy-dispersive X-ray spectroscopy and X-ray diffraction to understand the degradation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The investigations related to the corrosion of AM-prepared Ti alloys reviewed in this work are summarized in Table 6. [68][69]84,[113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] The work performed by Dai, et al, 84,113 analyzes the corrosion characteristics of Ti6Al4V alloys produced by SLM in different chloride-containing media. The authors evaluated the corrosion of SLM Ti6Al4V by altering exposed planes to different electrolytes 84 and by post-build heat treatments.…”
Section: Titanium Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigations related to the corrosion of AM-prepared Ti alloys reviewed in this work are summarized in Table 6. [68][69]84,[113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] The work performed by Dai, et al, 84,113 analyzes the corrosion characteristics of Ti6Al4V alloys produced by SLM in different chloride-containing media. The authors evaluated the corrosion of SLM Ti6Al4V by altering exposed planes to different electrolytes 84 and by post-build heat treatments.…”
Section: Titanium Alloysmentioning
confidence: 99%
“…The SLM Ti-TiB composite was compared to commercially pure Ti for corrosion performance in Hank's solution by Chen, et al 129 The presence of TiB phase facilitated the oxide layer deposition on the SLM Ti-TiB surface, which reduced the average i corr from 0.75 μA/cm 2 to 0.22 μA/cm 2 and increased the E pit from 0.70 V SCE to 1.23 V SCE . Hot corrosion of SLM Ti-Re was investigated by Majchrowicz, et al, 130 as function of rhenium (Re) content in a 75% Na 2 SO 4 /25% NaCl salt mix. Corrosion of SLM Ti-Re did not follow any trends with the increase of Re content.…”
Section: Titanium Alloysmentioning
confidence: 99%
“…Besides, Re is a β-isomorphous element with a hexagonal close-packed (HCP) lattice structure, which is known for improving the mechanical strength, recrystallization temperature and corrosion resistance of Ti alloys [86,102]. Chlebus et al [86] showed that 1.5 at% Re addition brings a significant strengthening effect to an LPBF-built Ti-Re alloy.…”
Section: Other Lam-based (α + β)-Ti Alloysmentioning
confidence: 99%
“…However, Re addition deteriorates the fatigue crack propagation resistance of CP-Ti due to the reduced ductility [103]. Majchrowicz et al [102] investigated the hot corrosion behaviour of LPBF Ti-xRe (x = 0, 2, 4 and 6 wt%) alloys in a mixed Na 2 SO 4 and NaCl salts at 600 • C. They reported that complete Re particle dissolution is essential to enhance the hot corrosion resistance of LPBF Ti-Re alloy.…”
Section: Other Lam-based (α + β)-Ti Alloysmentioning
confidence: 99%
“…The presence of this alcohol is interesting due to the statement of a theoretical study that rhenium can electrooxidize methanol by the bifunctional mechanism (32), without experimental comparisons. Rhenium is resistant to seawater corrosion and this metal has slow corrosion reaction in hydrogen and inert atmospheres at elevated temperatures (33). In addition, soluble oxide increased the corrosion resistance in the mild steel A537 (14).…”
Section: Introductionmentioning
confidence: 99%